2022
DOI: 10.48550/arxiv.2201.04169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuum, cyclotron line, and absorption variability in the high-mass X-ray binary Vela X-1

C. M. Diez,
V. Grinberg,
F. Fürst
et al.

Abstract: Because of its complex clumpy wind, prominent cyclotron resonant scattering features, intrinsic variability, and convenient physical parameters (close distance, high inclination, and small orbital separation), which facilitate the observation and analysis of the system, Vela X-1 is one of the key systems for understanding accretion processes in high-mass X-ray binaries on all scales. We revisit Vela X-1 with two new observations taken with NuSTAR at orbital phases ∼0.68-0.78 and ∼0.36-0.52, which show a pletho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…It should be noted that the so-called 10 keV broad absorption feature in Vela X-1 reported by the NuStar observations (e.g. Fürst et al 2014;Diez et al 2022) cannot be confirmed by the Insight-HXMT data. Thus, in the following spectral fitting, we only consider the Fe K emission feature in the band of 6 -10 keV.…”
Section: Phase Averaged Spectral Analysismentioning
confidence: 81%
“…It should be noted that the so-called 10 keV broad absorption feature in Vela X-1 reported by the NuStar observations (e.g. Fürst et al 2014;Diez et al 2022) cannot be confirmed by the Insight-HXMT data. Thus, in the following spectral fitting, we only consider the Fe K emission feature in the band of 6 -10 keV.…”
Section: Phase Averaged Spectral Analysismentioning
confidence: 81%